2019
DOI: 10.3390/ma12030366
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Different Electrical Parameters of Solar Cells with Silver Front Electrodes

Abstract: This work presents comparison results of the selected electrical parameters of silicon solar cells manufactured with silver front electrodes which were co-fired in an infrared belt furnace in the temperature range of 840–960 °C. The commercial paste (PV19B) was used for the metallization process. Electrical properties of a batch of solar cells fabricated in one cycle were investigated. Three methods were used, including measurement of the current-voltage characteristics (I-V), measurement of contacts’ resistiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The research conducted by the authors of the article on the change of electrical parameters of silicon through the use of neon ion implantation [29][30][31][32] has led to the development of the author's method for producing and identifying additional energy levels in the band structure of semiconductors. This direction fits perfectly into the current research trend and is in line with the market trends of increasing use of ion implantation in PV cell production [33,34].…”
Section: Current Research Directions Using Ion Implantationsupporting
confidence: 83%
“…The research conducted by the authors of the article on the change of electrical parameters of silicon through the use of neon ion implantation [29][30][31][32] has led to the development of the author's method for producing and identifying additional energy levels in the band structure of semiconductors. This direction fits perfectly into the current research trend and is in line with the market trends of increasing use of ion implantation in PV cell production [33,34].…”
Section: Current Research Directions Using Ion Implantationsupporting
confidence: 83%
“…Figure 4 shows the results of measurements of the electrical properties of the first series of photovoltaic cells [ 34 ]. Based on the results obtained by testing the electrical properties of this series of photovoltaic cells, it was found that the lowest values for resistance and resistivity were obtained from samples with a firing temperature of 940 °C for both methods (TLM and PD).…”
Section: List Of Test Results Performed With the Use Of The Tlm And Pd Methodsmentioning
confidence: 99%
“…As part of the experiment, the selected electrical parameters (i.e., resistance and resistivity of photovoltaic cells) were tested, and then, using the formulae contained in Table 1 , their values were determined [ 34 ]. In the TLM method, a row of five front electrodes (strip size—0.1 mm × 8 mm) with a variable distance between them (2.5; 5; 10; 30 mm) was used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations